A Predator-Prey Model with Functional Response and Stage Structure for Prey - Xiao-Ke Sun; Hai-Feng Huo; Xiao-Bing Zhang (Abstract and Applied Analysis)
A predator-prey system with Holling type II functional response and stage structure for prey is presented. The local and global stability are studied by analyzing the associated characteristic transcendental equation and using comparison theorem. The existence of a Hopf bifurcation at the positive equilibrium is also studied. Some numerical simulations are also given to illustrate our results.